Covalent Histone Modification by an Electrophilic Derivative of the Anti-HIV Drug Nevirapine - Harjivan, Shrika G. (2021)
Funding: This work was supported in part by the PRIME-XS project, grant agreement number 262067, funded by the European Union seventh Framework Programme. We also thank Fundação para a Ciência e a Tecnologia (FCT), Portugal, for financial support through projects UID/QUI/00100/2020 (to CQE), RECI/QEQ-MED/0330/2012 and PTDC/QUI-QAN/32242/2017, as well as contract CEECIND/02001/2017 (to A.M.M.A) and doctoral fellowships SFRH/BD/80690/2011 (to SGH), SFRH/BD/75426/2010 (to ILM), and SFRH/BD/102846/2014 (to CC). Joint funding from FCT and the COMPETE Program through grant SAICTPAC/0019/2015 and RNEM-LISBOA-01-0145- FEDER-022125 funding are also gratefully acknowledged. The CRG/UPF Proteomics Unit is part of the “Plataforma de Recursos Biomoleculares y Bioinformáticos (ProteoRed)” supported by grant PT13/0001 of the Instituto de Salud Carlos III (ISCIII).